Algoritma Algoritma K-Means Clustering untuk Mengklasifikasi Tingkat Kepuasan Layanan Informasi Hukum di Provinsi Jawa Barat: Algoritma K-Means Clustering untuk Mengklasifikasi Tingkat Kepuasan Layanan Informasi Hukum di Provinsi Jawa Barat - Beny Ruhiman; Ade Ramdan; Christina Juliane (Jurnal Komputer Terapan, 2022)
Legal Documentation and Information Network (JDIH) is one of the government agencies in the field of law, which is regulated by Presidential Regulation Number 33 of 2012. JDIH consists of central and regional levels, at the provincial level the Bureau of Law and Human Rights is the center of JDIH in its territory. JDIH at the provincial level has the duties and functions to provide guidance and evaluation at the members. To measure the level of community satisfaction with JDIH members in West Java, a survey was conducted using the 360 review ​​method on the website https://jdih.jabarprov.go.id/review.php/. The results contained 18,045 raw data. After preprocessing, 46 datasets and 11 attributes were generated. Cluster modeling uses the K-Means algorithm, the results are evaluated by the Davies Boulding Index (DBI) method. Evaluation results show a low level of similarity so that the distance between clusters is getting higher. On this study is classified into 4 clusters, the lowest satisfaction indicator is known to be in cluster 3 which consists of 10 regions. In this research can be used to determining policies for the government of West Java Province.